2015
DOI: 10.1111/srt.12237
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of infrared thermography for the prediction of postherpetic neuralgia in acute herpes zoster patients

Abstract: In this study, we showed that infrared thermography is useful as a predictor of PHN development in acute HZ patients but is not useful as an objective assessment tool for indicating subjective pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…During the study, it is possible to verify the change in the thermal gradient from its initial phase, to the final result of the therapeutic approach. The results observed in this case study are in agreement with the findings of Ko et al [9], who evaluated 112 individuals (46 men and 66 women) aged 9 to 93 years with herpes zoster, and observed that as the temperature difference between the affected and the contra lateral dermatome (ΔT) increased, the occurrence of PHN increased significantly. In the same sense, Han et al [10] evaluated 110 patients diagnosed with acute HZ, with the development of PHN and comorbidities.…”
Section: Discussionsupporting
confidence: 93%
“…During the study, it is possible to verify the change in the thermal gradient from its initial phase, to the final result of the therapeutic approach. The results observed in this case study are in agreement with the findings of Ko et al [9], who evaluated 112 individuals (46 men and 66 women) aged 9 to 93 years with herpes zoster, and observed that as the temperature difference between the affected and the contra lateral dermatome (ΔT) increased, the occurrence of PHN increased significantly. In the same sense, Han et al [10] evaluated 110 patients diagnosed with acute HZ, with the development of PHN and comorbidities.…”
Section: Discussionsupporting
confidence: 93%
“…These sticker-like sensors are used in sleep studies to help with the treatment of sleep disorders, jet lag, and pressure ulcers on a clinical bed setup. Distributed skin temperature mapping has also been demonstrated to study thermoregulation efficiency in athletic performance 25 , as well as dermatome abnormality through regional nerve root damage 26 . However, even though they are wireless, these epidermal sensors require a Near Field Communication (NFC) reader around the vicinity to power the electronics and collect the data.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used infrared thermography (IRT) to measure skin temperature during HZ-affected periods [15][16][17]. IRT is a noncontact imaging technique that uses an infrared camera to detect and visualize emitted body heat.…”
Section: Introductionmentioning
confidence: 99%